Microtubules in Pancreatic β Cells: Convoluted Roadways Toward Precision - Bracey, Kai M.; Gu, Guoqiang; Kaverina, Irina (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic islet β cells regulate glucose homeostasis via glucose-stimulated insulin secretion (GSIS). Cytoskeletal polymers microtubules (MTs) serve as tracks for transport and positioning of secretory insulin granules. MT network in β cells has unique morphology with several distinct features, which support their biogenesis (via Golgi-derived MT array), net non-directional transport (via interlocked MT mesh), and control availability of granules at secretion sites (via submembrane MT bundle). The submembrane MT array, which is parallel to the plasma membrane and serves to withdraw excessive granules from the secretion hot spots, is destabilized and fragmented downstream of high glucose stimulation, allowing for regulated secretion. The origin of such unusual MT network, detailed features that define its functionality, as well as metabolic pathways that regulate it, are still to a large extent elusive and are a matter of active investigation and debate. Besides the MT network itself, it is important to consider the interplay of molecular motors that drive and fine-tune insulin granule transport. Importantly, activity of kinesin 1, which is the major MT-dependent motor in β cells, transports insulin granules, and has a capacity to remodel MT network, is also regulated by glucose. We discuss yet unknown potential avenues toward understanding how MT network and motor proteins provide control for secretion in coordination with other GSIS-regulating mechanisms.